2012
DOI: 10.1007/s10518-012-9401-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving the spatial resolution of ground motion variability using earthquake and seismic noise data: the example of Bishkek (Kyrgyzstan)

Abstract: Site response analysis plays an important role in seismic hazard and risk assessment, and in defining the optimal engineering design for civil structures. However, due to increasing urbanization, target areas are often too vast to be covered by standard approaches, resulting in large uncertainties in the spatial variability of the expected ground motion. Here, we propose a method to improve the spatial resolution of ground motion variability in terms of Standard Spectral Ratios (SSRs), using earthquakes record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…(Left panel) Median response spectra. (Right panel) between-event (τ), between-site (φS2S), eventand-site corrected standard deviations (φ0) and the total aleatory variability (σ) of the GMPE in natural-log scale5 Spectral clustering analysisWith increasing amount of strong motion data, ground motion modelers are adapting advanced statistical tools to analyze large amounts of ground motion data to identify repeatable effects, evaluate parametrization, and quantify better the uncertainties in prediction (e.g Derras et al (2012),Ullah et al (2013),Luzi et al (2011)…”
mentioning
confidence: 99%
“…(Left panel) Median response spectra. (Right panel) between-event (τ), between-site (φS2S), eventand-site corrected standard deviations (φ0) and the total aleatory variability (σ) of the GMPE in natural-log scale5 Spectral clustering analysisWith increasing amount of strong motion data, ground motion modelers are adapting advanced statistical tools to analyze large amounts of ground motion data to identify repeatable effects, evaluate parametrization, and quantify better the uncertainties in prediction (e.g Derras et al (2012),Ullah et al (2013),Luzi et al (2011)…”
mentioning
confidence: 99%
“…Using earthquakes recorded at a few selected sites for a relatively short amount of time and seismic noise data collected over a denser grid, Ullah et al [2013] showed that the spatial resolution of ground motion variability in terms of SSRs can be significantly improved. Using a K-means algorithm, clusters of sites that display a similar response can be identified based on their similarity of the SSRs.…”
Section: Bishkek (Kyrgyzstan)mentioning
confidence: 99%
“…In the case of Bishkek, local amplification effects have been estimated at 19 different locations within the town, where seismic stations have been installed (Parolai et al, 2010;Ullah et al, 2012;see Fig. 3).…”
Section: Site Effectsmentioning
confidence: 99%
“…The site response is obtained by means of standard spectral ratio (Borcherdt, 1970) between the Fourier spectra of the recordings at the stations located in Bishkek and those of a reference station (Parolai et al, 2010). The site amplifications estimated in this way are affecting a wide frequency band (from nearly 0.2 Hz to a few hertz) and generally increase from south to north (Parolai et al, 2010;Ullah et al, 2012).…”
Section: Site Effectsmentioning
confidence: 99%